Experimental Investigation of Heat Transfer Characteristics of Louver and Wavy Fin Heat Exchangers of AHU using New Data Reduction Method - Wu Pengzhan; Gu Bo; Zeng Weijie (Zhileng xuebao)
An experimental investigation was conducted into the heat transfer performance of the fin-and-tube heat exchanger in an air handling unit (AHU), and calculation models were used to analyze the experimental data. The tube-by-tube and row-division methods were extended to process the experimental data under the heating conditions, and the fin-and-tube heat exchanger was analyzed in terms of the heat transfer performance of the air side. Compared with the traditional logarithmic mean temperature differenceand number of transfer units methods, the deviations of the j factorand heat transfer coefficient h calculated by the four methods were all within 10%. The effect of the j factor under different fin spacing, tube diameters, and the number of tube banks was studied. The results showed that the jfactor gradually decreased by 25.6% when increasing Re from 3 000 to 6 020. The j factor of a louver fin was larger than that of a wavy fin at the same Re, and the maximum deviation decreased from 26.3% to 8.3% with increasing Re. The j factor increased with increasing fin spacing and tube diameter and decreased with the number of tube banks. When there were eight tube banks, the j factor decreased sharply to approximately 0.008. The research provides a theoretical basis for the design optimization and operation of heat exchangers for AHUs.